2005
DOI: 10.1111/j.1600-0609.2005.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thrombocytopenia with disappearance of HCV RNA in patients treated by interferon‐α therapy: possible etiology of HCV‐associated immune thrombocytopenia

Abstract: We evaluated the relationship between the severity of thrombocytopenia and the serum hepatitis C virus (HCV) RNA level to investigate the mechanism of thrombocytopenia in patients with HCV infection. Patients who had chronic hepatitis without splenomegaly were divided into two groups according to the platelet count, which were 18 patients with a platelet count < or =150 x 10(9)/L and 22 patients with a platelet count >150 x 10(9)/L. HCV RNA, platelet-associated immunoglobulin G (PAIgG), rheumatoid factor (RF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…Platelet sequestration and destruction in the spleen [82,83] , along with low thrombopoetin production [83,84] play an important role in the pathogenesis of thrombocytopenia. However, a direct viral infection of the megakariocytes [85] and autoimmune mechanisms [86,87] cannot be ruled out. The higher prevalence of thrombocytopenia in cryoglobulinpositive than in cryoglobulin-negative patients (58.8% vs 15.3%, OR 7.9, 95% CI 3.5-17.8) in the present study may reflect the role of immune dysregulation in causing both abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet sequestration and destruction in the spleen [82,83] , along with low thrombopoetin production [83,84] play an important role in the pathogenesis of thrombocytopenia. However, a direct viral infection of the megakariocytes [85] and autoimmune mechanisms [86,87] cannot be ruled out. The higher prevalence of thrombocytopenia in cryoglobulinpositive than in cryoglobulin-negative patients (58.8% vs 15.3%, OR 7.9, 95% CI 3.5-17.8) in the present study may reflect the role of immune dysregulation in causing both abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Combination antiviral therapy with standard or pegylated interferon plus ribavirin is approved for the treatment of patients with chronic HCV who have compensated liver disease. Whereas antiviral treatment can result in improvement in the platelet count, [136][137][138] thrombocytopenia is a recognized side effect of interferon therapy. Manufacturers recommend that the presence of thrombocytopenia with a platelet count Ͻ 75 ϫ 10 9 /L is a relative contraindication to interferon therapy.…”
Section: Management Of Secondary Itp (Hcv-associated)mentioning
confidence: 99%
“…31 Four Approximately half of adult CITP patients with HCV treated with INF-α therapy responded with a rise in platelet count. 30,31,47,51 Four of 5 HCV-positive patients treated with interferon-alpha (IFN-α) responded with increased platelet counts. 41,47 Responders to IFN-α could be distinguished from the non-responder by a decrease in HCV quantitative RNA, hepatic transaminases and cryoglobulins.…”
Section: Treatmentmentioning
confidence: 99%
“…30 Iga et al reported significant increases in the platelet counts of 12 HCV infected patients who were complete responders to interferon alpha (IFN-α) treatment, but no improvement in the platelet counts of 11 patients who failed IFN-α therapy assessed by viral load. 51 In a recent Phase II study, eltrombopag, an oral thrombopoietin receptor agonist, increased platelet counts in the majority of patients with cirrhosis associated with HCV infection to >100 × 10 9 /L and allowed for effective IFN-based therapy. 52 Response was dose-dependent, with 9/17 (53%) responding to 30 mg/day, 15/19 (79%) to 50 mg/day and 20/21 (95%) to 75 mg/day.…”
Section: Treatmentmentioning
confidence: 99%